Long-Term Effect of Post-traumatic Stress in Adolescence on Dendrite Development and H3K9me2/BDNF Expression in Male Rat Hippocampus and Prefrontal Cortex - Zhao, Mingyue; Wang, Wei; Jiang, Zhijun; Zhu, Zemeng; Liu, Dexiang; Pan, Fang (Frontiers in Cell and Developmental Biology, 2020)
Exposure to a harsh environment in early life increases in the risk of post-traumatic stress disorder (PTSD) of an individual. Brain derived neurotrophic factor (BDNF) plays an important role in neurodevelopment in developmental stages. Both chronic and traumatic stresses induce a decrease in the level of BDNF and reduce neural plasticity, which is linked to the pathogenesis of PTSD. Also, studies have shown that stress alters the epigenetic marker H3K9me2, which can bind to the promoter region of the Bdnf gene and reduce BDNF protein level. However, the long-term effects of traumatic stress during adolescence on H3K9me2, BDNF expression and dendrite development are not well-known. The present study established a model of PTSD in adolescent rats using an inescapable foot shock (IFS) procedure. Anxiety-like behaviors, social interaction behavior and memory function were assessed by the open field test, elevated plus maze test, three-chamber sociability test and Morris water maze test. In addition, neuronal development and H3K9me2/BDNF expression in hippocampus (HIP) and prefrontal cortex (PFC) were evaluated by Golgi staining, Western blotting, qRT-PCR analysis and CHIP-qPCR analysis. Additionally, the Unc0642, a small molecule inhibitor of histone methyltransferase (EHMT2) was used for intervention. The results showed that the IFS procedure induced the PTSD-like behaviors in rats, resulted in fewer dendrite branches and shorter dendrite length in CA1 of HIP and PFC, increased H3K9me2 level and decreased BDNF expression in HIP and PFC. Also, although all the changes can persist to adulthood, Unc0642 administration relieved most of alterations. Our study suggests that traumatic stress in adolescence leads to immediate and long-term mental disorders, neuronal morphological changes, lower BDNF level and increased H3K9me2 level in the HIP and PFC, indicating that H3K9me2/BDNF dysfunction plays a key role in pathogenesis of PTSD.